The increasing burden of imported chronic hepatitis B--United States, 1974-2008. - Tarissa Mitchell; Gregory L Armstrong; Dale J Hu; Annemarie Wasley; John A Painter (PLoS ONE, 2011)
Without intervention, up to 25% of individuals chronically infected with hepatitis B virus (HBV) die of late complications, including cirrhosis and liver cancer. The United States, which in 1991 implemented a strategy to eliminate HBV transmission through universal immunization, is a country of low prevalence. Approximately 3,000-5,000 U.S.-acquired cases of chronic hepatitis B have occurred annually since 2001. Many more chronically infected persons migrate to the United States yearly from countries of higher prevalence. Although early identification of chronic HBV infection can reduce the likelihood of transmission and late complications, immigrants are not routinely screened for HBV infection during or after immigration.To estimate the number of imported cases of chronic hepatitis B, we multiplied country-specific prevalence estimates by the yearly number of immigrants from each country during 1974-2008.During 1974-2008, 27.9 million immigrants entered the U.S. Sixty-three percent were born in countries of intermediate or high chronic hepatitis B prevalence (range 2%-31%). On average, an estimated 53,800 chronic hepatitis B cases were imported to the U.S. yearly from 2004 through 2008. The Philippines, China, and Vietnam contributed the most imported cases (13.4%, 12.5%, and 11.0%, respectively). Imported cases increased from an estimated low of 105,750 during the period 1974-1977 to a high of 268,800 in 2004-2008.Imported chronic hepatitis B cases account for approximately 95% of new U.S. cases. Earlier case identification and management of infected immigrants would strengthen the U.S. strategy to eliminate HBV transmission, and could delay disease progression and prevent some deaths among new Americans.